2013
DOI: 10.1038/ncb2886
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy variation within a cell population determines cell fate through selective degradation of Fap-1

Abstract: Autophagy regulates cell death both positively and negatively, but the molecular basis for this paradox remains inadequately characterized. We demonstrate here that transient cell-to-cell variations in autophagy can either promote cell death or survival depending on the stimulus and cell type. By separating cells with high and low basal autophagy by flow cytometry, we demonstrate that autophagy determines which cells live or die in response to death receptor activation. We have determined that selective autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
159
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(161 citation statements)
references
References 51 publications
0
159
1
1
Order By: Relevance
“…61,62 The mCherry-GFP-LC3 plasmid encoding the tandem fluorescent reporter was generated in the laboratory of Dr. Terje Johansen 63 and obtained from Add gene (plasmid 22418). Cultured HK-2 cells seeded in cover glass-bottom dishes were transfected with mCherry-GFP-LC3 plasmid using Lipofectamine 2000 (Invitrogen, 11668-019) for 24 h. After the designated treatments, live cell images were obtained using a DeltaVision microscope imaging system (Applied Precision, Issaquah, WA, USA).…”
Section: Mcherry-gfp-lc3 Plasmid Transfectionmentioning
confidence: 99%
“…61,62 The mCherry-GFP-LC3 plasmid encoding the tandem fluorescent reporter was generated in the laboratory of Dr. Terje Johansen 63 and obtained from Add gene (plasmid 22418). Cultured HK-2 cells seeded in cover glass-bottom dishes were transfected with mCherry-GFP-LC3 plasmid using Lipofectamine 2000 (Invitrogen, 11668-019) for 24 h. After the designated treatments, live cell images were obtained using a DeltaVision microscope imaging system (Applied Precision, Issaquah, WA, USA).…”
Section: Mcherry-gfp-lc3 Plasmid Transfectionmentioning
confidence: 99%
“…For example, we have previously shown that basal autophagy affects cell fate in response to pro-death stimuli. 1,2 Moreover, some cancer cells are dependent on basal levels of autophagy for survival. 3 While many mechanisms that control the induction of autophagy have been characterized, the regulation of basal autophagy is incompletely understood.…”
Section: Basal Autophagy Is Negatively Regulated By Rip1mentioning
confidence: 99%
“…Partial knockdown of RIP1 increased the sensitivity of MCF10A cells to FasL but protected from TRAIL-induced cell death in a manner dependent on increases in autophagy, consistent with our previous observations that higher basal autophagy selectively potentiates Fas ligand mediated cell death while inhibiting TRAIL-mediated cell death. 1 RIP1 has previously been shown to play multiple roles related to cell death signaling. In addition to its ability to activate MAP kinases, such as JNK, p38, and ERK, RIP1 is also important for the activation of pro-survival signals through NF-kB-mediated transcription.…”
Section: Basal Autophagy Is Negatively Regulated By Rip1mentioning
confidence: 99%
“…Autophagy has been found to be implicated in various human diseases and can either promote cell survival or cell death (Kroemer and Levine 2008; Gump et al 2014). In different cellular contexts, a complex of signalling pathways controls the activation of autophagy (Zhu et al 2007; Maiuri et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on morphology, three major types of programmed cell death have been coined: apoptosis, autophagic cell death and programmed necrosis (Eisenberg-Lerner et al 2009). Under oxidative stress, ROS including free radicals, such as superoxide, hydroxyl radical and hydrogen peroxide are generated at high levels leading to cellular damage and cell death (Gump et al 2014). This kind of cell death often involves induction of apoptosis through caspase activation.…”
Section: Introductionmentioning
confidence: 99%